Peculiarities of coagulation hemostasis disorders in patients with chronic obstructive pulmonary disease. - Yakovlieva, V. H. (Medicni Perspektivi, 2015)
.The violation of blood coagulation properties is observed in many diseases of the respiratory system, including chronic obstructive pulmonary disease (COPD). It is known that in a stable COPD phase release of proinflammatory cytokines in blood is observed, it leads to disturbance of hemostasis parameters toward hypercoagulation. The aim of our study was to determine possibility of coagulation disorders formation in patients with COPD in a stable phase of pathological process at different stages of disease course and identify relationship between coagulation parameters levels and degree of violation of ventilation lung function. Materials and methods. We examined 30 patients with COPD in a stable disease phase, included in the main group (FEV1 =49,5±15,5% of the due, there were 27 men (90.0%), 3 (30.0%) women, mean age was 61,8±7,9 years, level of pack /years index - 34,2±15,3). The control group consisted of 10 healthy subjects matched with the patients of the main group by age and sex. All patients were divided into 2 subgroups. Subgroup 1 included 16 patients with moderate COPD, that is the level of FEV1>50% (61,8±7,4% of predicted), and subgroup 2 - 14 COPD patients with severe COPD, that is the level of FEV1 <50% (35,3±8,2% of predicted). Patients received standard treatment according to the disease stage. Main indicators of coagulation levels: prothrombin index (PI), prothrombin ratio (PR), international normalized ratio (INR), activated partial thromboplastin time (APTT), thrombin time (TT) and antithrombin III (AT III) were identified in all patients. Results. The levels of PI, PR and INR in the subgroup 1 differed significantly from those of in the subgroup 2, control group (p<0,05) and pointed at hypercoagulation, whereas in the subgroup 2 all indicators were absolutely identical with control group. Correlation link between the level of INR levels and FEV1 (r=-0,73; p<0.01) in patients of the main group was determined. Levels of APTT, TT and AT III in the main group and in subgroups 1 and 2 were identical to those of the control group. There were no significant differences of these parameters between subgroups 1 and 2. Conclusions. In patients with COPD already at early stage of the disease abnormalities of coagulation hemostasis link mainly on external coagulation pathway toward hypercoagulation develop.